Lahopuusto monimuotoisuuden ja luonnontilaisuuden osatekijänä Etelä-Suomen ja Karjalankannaksen vanhoissa kuusimetsiköissä - Luomi, Annukka (Helsingfors universitet, 2007)
Coarse woody debris (CWD) is an important structural element in boreal forests affecting various ecological processes and maintaining biodiversity. Numerous species are dependent on spatiotemporal availability of CWD and its diverse characteristics. Forest management has drastically reduced the amount of CWD, thus impoverishing the structural diversity and threatening several species in the boreal forest ecosystems. The aim of this study was to assess the diversity and naturalness of old-growth spruce forest stands in southern Finland and the Karelian Isthmus based on the amount and quality of CWD. Prior to the Second World War forests in both regions were managed similarly. However, after the war the Karelian Isthmus became part of the Soviet Union (and later on Russia), and extensive economic utilization declined. Instead, efficient forest management practices were introduced in Finland after the war. Because southern Finland and the Karelian Isthmus belong to the same biogeographical region, the regional differences in the stand structure of the old-growth forests are mainly due to the differences in their land-use history. Ten old-growth spruce forest stands were studied both in southern Finland and the Karelian Isthmus. The Finnish stands were on areas that belong to Natura 2000 Network of the European Union. The Karelian stands were not protected, but five of them were on a planned protection area. Five 10 x 10 m plots were systematically established on a 9-ha square area in each forest stand. All CWD inside the plot and at minimum 10 cm in diameter was recorded. The length and the diameter at both ends or at breast height were measured. Also the position, decay class and tree species of each piece were noted. The amount and quality of CWD varied widely within and between the forest stands, and there were only few clear differences at the regional level. The average volume of CWD was 105,8 m3/ha (19,6-224,4 m3/ha) in southern Finland and 85,4 m3/ha (13,6-144,6 m3/ha) in the Karelian Isthmus. In southern ...